Private Rates of Return to Higher Education for Women - Hoffer, Stefan N. (The Review of Economics and Statistics, 1973)
SINCE World War II there has been a tremendous increase in the number of men and women attending college, an increase in the attachment of women to the labor force, and more recently, widespread concern with the economic position of women. Despite these developments, there has been little investigation of the impact of higher education on women's earnings.' This study undertakes such an investigation. Its scope will be limited to considering only monetary costs and benefits associated with education since only these can be measured directly.